2015
DOI: 10.1016/j.poly.2015.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and lanthanide coordination chemistry of CMPO-decorated dibenzothiophene and dibenzothiophene sulfone platforms

Abstract: New hybrid donor ligands based on the dibenzothiophene and dibenzothiophene-5,5-dioxide platforms decorated with C-attached carbamoylmethylphosphine oxide substituents have been prepared. The potential chelation behavior of the ligands has been explored with molecular mechanics calculations and selected coordination chemistry with Ln(NO 3) 3 salts examined. The acid dependence of the solvent extraction performance of the dibenzothiophene-5,5-dioxide derivative for Am(III) and Eu(III) has also been surveyed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Solvent extraction studies showed that (36 X = SO 2 ) was better performing than (37 X = SO 2 ) [104] and that (37 X = O) is a stronger extractant than (36 X = O) [103]. Complexes of (38 X = S) (Ln = La, Pr, Eu, Er, Lu) are tetradentate on the basis of infrared spectroscopy in [Ln(NO 3 ) 3 (38)], whilst the coordination mode of (38 X = SO 2 ) is unclear due to overlap of bands in the spectra [105]. The crystal structure with X = SO shows that in [Eu(NO 3 ) 3 (38)], (38) bonds via both PO and the SO oxygen atoms with the amide carbonyl groups not bonded to the metal.…”
Section: Complexes With Lanthanide Nitratesmentioning
confidence: 99%
“…Solvent extraction studies showed that (36 X = SO 2 ) was better performing than (37 X = SO 2 ) [104] and that (37 X = O) is a stronger extractant than (36 X = O) [103]. Complexes of (38 X = S) (Ln = La, Pr, Eu, Er, Lu) are tetradentate on the basis of infrared spectroscopy in [Ln(NO 3 ) 3 (38)], whilst the coordination mode of (38 X = SO 2 ) is unclear due to overlap of bands in the spectra [105]. The crystal structure with X = SO shows that in [Eu(NO 3 ) 3 (38)], (38) bonds via both PO and the SO oxygen atoms with the amide carbonyl groups not bonded to the metal.…”
Section: Complexes With Lanthanide Nitratesmentioning
confidence: 99%
“…Interestingly, DBT-6 was stable towards air oxidation, but underwent partial oxidation once coordinated with Ln(III) ions. 148…”
Section: Chart 12mentioning
confidence: 99%
“…A similar approach was recently employed in the assessment of chelate preferences for ligands derived from pyridine N-oxide platforms decorated with CMPO pendent arms. [18] Z. Anorg As a point of reference, the 1:1 binding of the parent NOPO fragment 3a on Gd III was evaluated, and a view of the lowest energy complexed form is shown in Figure 1a.…”
Section: Computational Assessment Of the Chelation Properties Of 5 Andmentioning
confidence: 99%